Pemikiran Ibnu Qayyim Al Jauziyyah Tentang Pendidikan Anak Usia Dini - Fitri Ramadhini (IAIN Padangsidimpuan, 2021)
In this research, the background is how to educate children from an early age. In educating early childhood is one that must be developed with all its potential. Therefore,in the scope of the family in early childhood, he gets his first education is both parents, who have been given the mandate also responsibility. But the reality is sometimes parents lack interaction with their children and also their sense of caring. So that children also do not have a good interaction with parents, families, people, and the environment. The method used in research is the method of library research (Library Research), with a qualitative approach. Of the problems discussed, the researcher uses a philosophical approach. So that the object of research is the thought of early childhood education according to Ibnu Qayyim Al Jauziyyah. In data collection techniques, the researchers used documentation materials. And the researchers themselves are the core instrument. Researchers use content analysis (content analysis). Based on the results of early childhood education research according to Ibn Qayyim's thinking is very important for children's education from an early age.